Religious infrastructure: establishing a research agenda - Hölzchen, Yanti (Religion, state & society, 2024)
This collection sets out to establish a distinct research agenda around the notion of religious infrastructure, creating an interface between the study of religion and that of infrastructure which enriches both fields. To this end, we bring together eight contributions by a multidisciplinary group of scholars who are conducting empirical research in diverse global contexts. Each of these contributions stages a generative conversation between the concept of religious infrastructure and their empirical findings. Collectively, we explore and further develop the analytical potential of religious infrastructure as a lens and unit of analysis for future research on religion and infrastructure alike.